Tapestry writing 4 : A revised edition of. The newbury house guide to writing - Sokolik, M. E. (Heinle & Heinle, 2000)
Engaging writing and reading activities, integrated grammar instruction, languaje learning and academic power strategies, CNN videos, and a Web site effective prepare students to be sucessful, independent learners.